The limitations of the application of the concept of Energy Poverty in Peru - Villegas Vega, Paul (2021)
This study provides a legal approach to the concept of energy poverty and its main characteristics to be adequately addressed by the economic administrative law. The multidimensional approach to energy poverty is established in the Peruvian legal system based on the normative experience and public policies undertaken by this country in the electricity and natural gas sectors. The study notes notable progress in reducing the energy poverty gap, but also some challenges that still need to be addressed in order to effectively reduce it.